1989
DOI: 10.1038/342561a0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo priming of virus-specific cytotoxic T lymphocytes with synthetic lipopeptide vaccine

Abstract: Cytotoxic T lymphocytes (CTL) constitute an essential part of the immune response against viral infections. Such CTL recognize peptides derived from viral proteins together with major histocompatibility complex (MHC) class I molecules on the surface of infected cells, and usually require in vivo priming with infectious virus. Here we report that synthetic viral peptides covalently linked to tripalmitoyl-S-glycerylcysteinyl-seryl-serine (P3CSS) can efficiently prime influenza-virus-specific CTL in vivo. These l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
276
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 609 publications
(285 citation statements)
references
References 25 publications
6
276
1
2
Order By: Relevance
“…It was discovered in the late 1980s that conjugation of Pam3CSS (tripalmitoyl Cys-SerSer) or Pam2CSS (di-O-acylated palmitoyl Cys-Ser-Ser) to peptides derived from bacterial or viral proteins could convert the immunologically inactive peptides into potent vaccines that provided long-lasting protection against bacterial or viral infections in animal models. This effect was enabled by induction of neutralizing antibodies (28,29) and by in vivo priming of epitope-specific cytotoxic T cells and memory T cells (30)(31)(32). Since antibodies to the lipid moieties are not generated in vivo, the immune-enhancing effect of the lipids is believed to be similar to that of a conventional adjuvant, and thus, bacterial lipoprotein/lipopeptidecontaining vaccines are recognized as one category of selfadjuvanting vaccines (21)(22)(23)33).…”
Section: Immune-enhancing Effects Of the N-terminal Lipids Of Rlp2086mentioning
confidence: 99%
“…It was discovered in the late 1980s that conjugation of Pam3CSS (tripalmitoyl Cys-SerSer) or Pam2CSS (di-O-acylated palmitoyl Cys-Ser-Ser) to peptides derived from bacterial or viral proteins could convert the immunologically inactive peptides into potent vaccines that provided long-lasting protection against bacterial or viral infections in animal models. This effect was enabled by induction of neutralizing antibodies (28,29) and by in vivo priming of epitope-specific cytotoxic T cells and memory T cells (30)(31)(32). Since antibodies to the lipid moieties are not generated in vivo, the immune-enhancing effect of the lipids is believed to be similar to that of a conventional adjuvant, and thus, bacterial lipoprotein/lipopeptidecontaining vaccines are recognized as one category of selfadjuvanting vaccines (21)(22)(23)33).…”
Section: Immune-enhancing Effects Of the N-terminal Lipids Of Rlp2086mentioning
confidence: 99%
“…The recognition that peptides derived from viruses, bacteria, or classical parasites are presented to T-cells via MHC class I or class II molecules immediately suggested that instead of live, and therefore potentially harmful, infectious agents, peptides could possibly be used as vaccines to induce T-cell responses [80]. This was first formally shown for virus-specific peptides in studies by M. Schultz, P. Aichele, and H. Hengartner [81] ( Table 2, Fig.…”
Section: New Vaccinesmentioning
confidence: 99%
“…Furthermore, attachment of a lipophilic tail to the conjugate may improve the uptake and appropriate processing. On the other hand, the use of lipophilic compounds may complicate the manufacturing and purification of the vaccine [18,20]. Indeed, a most recent study in mice indicates that both the linkage of the two T cell epitopes and the modification with a lipo-tail (lipopeptides) strongly enhanced the immunogenicity of a peptidebased vaccine.…”
Section: Vaccination With a Th-and An Hiv-ctl Epitope 21mentioning
confidence: 99%